Metal surface treatment method

By introducing a Ti/Co/Zr intermediate layer and thermal diffusion treatment of W element on the surface of martensitic stainless steel, the problems of insufficient corrosion resistance and poor wear resistance of martensitic stainless steel in harsh environments are solved, and remarkable resistance is achieved. Improved corrosion and wear resistance.

CN118326326BActive Publication Date: 2025-01-21FOSHAN YIZHONG METAL MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410452491.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-15
Publication Date
2025-01-21
Estimated Expiration
2044-04-15

AI Technical Summary

Technical Problem

Martensite stainless steel has insufficient corrosion resistance in harsh corrosion environments, is sensitive to micro-moving fatigue damage, has low hardness and poor wear resistance.

Method used

By introducing the Ti/Co/Zr intermediate layer, a solid solution is formed between the metal matrix and Ti/Co/Zr, and a variety of stable compounds are formed on the surface. W element penetrates into the Ti/Co/Zr intermediate layer through thermal diffusion, improving the density and uniformity of the infiltrated layer.

Benefits of technology

The corrosion resistance and wear resistance of the metal matrix are significantly improved, and the bonding performance of the W layer and the overall performance of the metal matrix are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004793097630000091
    Figure BDA0004793097630000091
  • Figure BDA0004793097630000101
    Figure BDA0004793097630000101
Patent Text Reader

Abstract

The present invention relates to a metal surface treatment method, belonging to the technical field of metal processing. A metal surface treatment method comprises the following steps: 1) adding a metal matrix to acetone for soaking, adding anhydrous ethanol for ultrasonic treatment after drying, and drying; 2) ultrasonic rolling the clean metal matrix; 3) performing secondary alloying treatment on the surface of the pretreated metal matrix; the metal elements of the first alloying treatment are Ti, Co and Zr; the metal element of the second alloying treatment is W; 4) performing ion nitriding treatment on the alloyed metal matrix, and then obtaining. The present invention infiltrates Ti, Co and Zr elements into the metal matrix and uses them as an intermediate layer, so that the elements of each layer are distributed in a gradient, thereby improving the bonding performance of the wear-resistant layer and the corrosion resistance of the metal matrix. The W element infiltrates the Ti / Co / Zr intermediate layer by thermal diffusion, and through a high-temperature-low-temperature method, the W element quickly infiltrates, while helping to refine the grains and improve its wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal processing and relates to a metal surface treatment method. Background Art

[0002] Martensitic stainless steel has a wide range of applications in the industrial field due to its relatively low price, excellent mechanical properties and outstanding corrosion resistance. In particular, it can be seen in key industrial sectors such as aviation, electricity, petroleum, chemical industry and machinery. For example, martensitic stainless steel plays an irreplaceable role in the manufacture of rotating parts such as blades of industrial power devices (such as aircraft engines, industrial fans and turbine blades).

[0003] However, martensitic stainless steel also has some inherent defects, such as relatively low hardness, poor wear resistance, and high sensitivity to fretting fatigue damage. Especially in the case of low Zr content, such as 2Zr13 martensitic stainless steel, its corrosion resistance in harsh corrosive environments is particularly insufficient.

[0004] In order to overcome these defects, double-layer glow plasma surface alloying technology came into being. With its many advantages such as fast infiltration rate, good density of infiltration layer, high bonding strength with the matrix, and green and pollution-free, this technology gives the matrix material excellent performance in terms of high temperature, wear, oxidation, corrosion, etc., thus significantly improving the use value and application scope of the material. Summary of the invention

[0005] The object of the present invention is to provide a metal surface treatment method. The present invention forms a solid solution between a metal matrix and Ti / Co / Zr by introducing a Ti / Co / Zr intermediate layer, and forms a compound with multiple stable components on its surface. Ti, Co and Zr elements have good corrosion resistance in various environments, so they are compounded as an intermediate layer, so that the elements of each layer are distributed in a gradient, thereby improving the bonding performance of the W layer and the corrosion resistance of the metal matrix.

[0006] In addition, the W element infiltrates into the Ti / Co / Zr intermediate layer through thermal diffusion. The higher temperature in the front section facilitates the rapid infiltration of the W element and increases the thickness of the infiltration layer. The lower temperature in the rear section helps to refine the grains, improve the density and uniformity of the infiltration layer, improve the wear resistance of the metal material, and reduce segregation.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A metal surface treatment method, the treatment method comprising the following steps:

[0009] 1) adding a metal substrate into acetone for soaking, drying the metal substrate, adding anhydrous ethanol for ultrasonic treatment, and drying the metal substrate to obtain a clean metal substrate;

[0010] 2) performing ultrasonic rolling on the clean metal substrate to obtain a pretreated metal substrate;

[0011] 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0012] 4) After the alloyed metal substrate is subjected to ion nitriding treatment, a metal finished product is obtained.

[0013] As a preferred technical solution of the present invention, in step 1), the mass ratio of the metal matrix, acetone and anhydrous ethanol is 12:45-60:50-65.

[0014] As a preferred technical solution of the present invention, in step 1), the immersion time is 30-45 minutes; the ultrasonic treatment conditions are 40-50°C temperature, 300-400kHz ultrasound for 5-10 minutes; the present invention removes various oil stains and dust adsorbents on the surface of the metal substrate by using acetone and anhydrous ethanol, which are organic agents with large polarity differences.

[0015] As a preferred technical solution of the present invention, the metal matrix is ​​2Zr13 martensitic stainless steel.

[0016] As a preferred technical solution of the present invention, in step 2), the ultrasonic rolling process parameters are: working static pressure is 350-450N, output amplitude is 8-10μm, spindle speed is 150-220r / min, lateral feed rate is 0.1-0.5mm / min, rolling times is 3-4 times, and the diameter of the rolling ball is 10-20mm; the texture of the present invention after ultrasonic rolling process can effectively improve the migration efficiency of the deposited atoms of the alloying layer, expand the contact range of the alloying metal elements with the substrate surface, and construct a mechanically inlaid interface structure. This change has a significant effect on enhancing the bonding strength between the alloying layer and the substrate.

[0017] As a preferred technical solution of the present invention, in step 3), the first alloying treatment adopts double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon gas pressure 35Pa, time 3h, temperature 670-700℃; the source target material is composed of Ti, Co and Zr in a mass ratio of 2:1:3.0-4.5, and the diameter of the source target material is 40mm and the thickness is 3mm; there is a significant difference in the melting point between stainless steel and W, and at the same time, the large difference in thermal expansion coefficient, atomic radius and electronegativity between the two also limits the solid solution diffusion capacity between them. These factors work together to limit the bonding force between the W element and the stainless steel matrix to a certain extent; the present invention uses Ti, Co and Zr to infiltrate the surface of the metal matrix as an intermediate layer to provide support, which is conducive to improving the bonding between the coatings, and can effectively improve the corrosion resistance of the metal matrix, while making the metal matrix less likely to crack.

[0018] As a preferred technical solution of the present invention, in step 3), the second alloying treatment adopts double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon gas pressure 38Pa, front period 2h, temperature 800-820℃, rear period 1h, temperature 750-780℃; the source target is W, the diameter of the source target is 40mm, and the thickness is 3mm.

[0019] As a preferred technical solution of the present invention, in step 4), the nitriding treatment process parameters are: voltage 800V, temperature 800°C, time 8h, and the volume ratio of hydrogen to nitrogen is 3:1.

[0020] Beneficial effects of the present invention:

[0021] The present invention introduces a Ti / Co / Zr intermediate layer, so that not only a solid solution can be formed between the metal matrix and Ti / Co / Zr, but also the addition of Ti, Co and Zr can form a compound with multiple stable components on its surface. The elements Ti, Co and Zr have good corrosion resistance under various environments. Therefore, the addition of Ti, Co and Zr as the intermediate layer makes the elements of each layer present a gradient distribution, which is not only beneficial to improving the bonding strength of the W layer, but also improves the corrosion resistance of the metal matrix.

[0022] In addition, the W element penetrates into the Ti / Co / Zr intermediate layer by thermal diffusion. In this process, the temperature of the front section is higher, which is conducive to the rapid penetration of the W element and increases the thickness of the diffusion layer. The temperature of the front section is lower than that of the front section, which helps to refine the grains and improve the density, uniformity and interlayer bonding of the diffusion layer. It can also effectively improve the wear resistance of the metal material surface and effectively reduce the segregation of the material. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0024] The technical solution of the present invention:

[0025] A metal surface treatment method comprises the following steps:

[0026] 1) adding a metal substrate into acetone for soaking, drying the metal substrate, adding anhydrous ethanol for ultrasonic treatment, and drying the metal substrate to obtain a clean metal substrate;

[0027] In step 1), the soaking time is 30-45 minutes; the ultrasonic treatment conditions are 40-50°C temperature, 300-400kHz ultrasound for 5-10 minutes; the mass ratio of the metal matrix, acetone and anhydrous ethanol is 12:45-60:50-65; the metal matrix is ​​2Zr13 martensitic stainless steel;

[0028] 2) performing ultrasonic rolling on the clean metal substrate to obtain a pretreated metal substrate;

[0029] In step 2), the ultrasonic rolling process parameters are: working static pressure is 350-450N, output amplitude is 8-10μm, spindle speed is 150-220r / min, lateral feed is 0.1-0.5mm / min, rolling times is 3-4 times, and the diameter of the rolling ball is 10-20mm;

[0030] 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0031] In step 3), the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the first alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon pressure 35Pa, time 3h, temperature 670-700℃; the source target is composed of Ti, Co and Zr in a mass ratio of 2:1:3.0-4.5, and the diameter of the source target is 40mm and the thickness is 3mm; the second alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon pressure 38Pa, the first period of time 2h, temperature 800-820℃, the second period of time 1h, temperature 750-780℃; the source target is W, and the diameter of the source target is 40mm and the thickness is 3mm;

[0032] 4) After the alloyed metal substrate is subjected to ion nitriding treatment, a metal finished product is obtained;

[0033] In step 4), the nitriding process parameters are: voltage 800 V, temperature 800° C., time 8 h, and the volume ratio of hydrogen to nitrogen is 3:1.

[0034] Example 1

[0035] A metal surface treatment method comprises the following steps:

[0036] 1) adding a metal substrate into acetone for soaking, drying the metal substrate, adding anhydrous ethanol for ultrasonic treatment, and drying the metal substrate to obtain a clean metal substrate;

[0037] In step 1), the immersion time is 30 minutes; the ultrasonic treatment conditions are 40°C temperature, 300kHz ultrasound for 5 minutes; the mass ratio of the metal matrix, acetone and anhydrous ethanol is 12:45:50; the metal matrix is ​​2Zr13 martensitic stainless steel;

[0038] 2) performing ultrasonic rolling on the clean metal substrate to obtain a pretreated metal substrate;

[0039] In step 2), the ultrasonic rolling process parameters are: working static pressure of 350N, output amplitude of 8μm, spindle speed of 150r / min, lateral feed of 0.1mm / min, rolling times of 3 times, and rolling ball diameter of 10mm;

[0040] 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0041] In step 3), the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the first alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon pressure 35Pa, time 3h, temperature 670℃; the source target material is composed of Ti, Co and Zr in a mass ratio of 2:1:3.0, and the diameter of the source target material is 40mm and the thickness is 3mm; the second alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon pressure 38Pa, the first period of time 2h, temperature 800℃, the second period of time 1h, temperature 750℃; the source target material is W, and the diameter of the source target material is 40mm and the thickness is 3mm;

[0042] 4) After the alloyed metal substrate is subjected to ion nitriding treatment, a metal finished product is obtained;

[0043] In step 4), the nitriding process parameters are: voltage 800 V, temperature 800° C., time 8 h, and the volume ratio of hydrogen to nitrogen is 3:1.

[0044] Example 2

[0045] A metal surface treatment method comprises the following steps:

[0046] 1) adding a metal substrate into acetone for soaking, drying the metal substrate, adding anhydrous ethanol for ultrasonic treatment, and drying the metal substrate to obtain a clean metal substrate;

[0047] In step 1), the immersion time is 38 minutes; the ultrasonic treatment conditions are 45°C temperature, 350kHz ultrasound for 8 minutes; the mass ratio of the metal matrix, acetone and anhydrous ethanol is 12:52:58; the metal matrix is ​​2Zr13 martensitic stainless steel;

[0048] 2) performing ultrasonic rolling on the clean metal substrate to obtain a pretreated metal substrate;

[0049] In step 2), the ultrasonic rolling process parameters are: working static pressure is 400N, output amplitude is 9μm, spindle speed is 185r / min, lateral feed is 0.3mm / min, rolling times is 3 times, and the diameter of the rolling ball is 15mm;

[0050] 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0051] In step 3), the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the first alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon gas pressure 35Pa, time 3h, temperature 685℃; the source target material is composed of Ti, Co and Zr in a mass ratio of 2:1:3.8, and the diameter of the source target material is 40mm and the thickness is 3mm; the second alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon gas pressure 38Pa, the first period of time 2h, temperature 810℃, the second period of time 1h, temperature 765℃; the source target material is W, and the diameter of the source target material is 40mm and the thickness is 3mm;

[0052] 4) After the alloyed metal substrate is subjected to ion nitriding treatment, a metal finished product is obtained;

[0053] In step 4), the nitriding process parameters are: voltage 800 V, temperature 800° C., time 8 h, and the volume ratio of hydrogen to nitrogen is 3:1.

[0054] Example 3

[0055] A metal surface treatment method comprises the following steps:

[0056] 1) adding a metal substrate into acetone for soaking, drying the metal substrate, adding anhydrous ethanol for ultrasonic treatment, and drying the metal substrate to obtain a clean metal substrate;

[0057] In step 1), the immersion time is 45 minutes; the ultrasonic treatment conditions are 50°C temperature, 400kHz ultrasound for 10 minutes; the mass ratio of the metal matrix, acetone and anhydrous ethanol is 12:60:65; the metal matrix is ​​2Zr13 martensitic stainless steel;

[0058] 2) performing ultrasonic rolling on the clean metal substrate to obtain a pretreated metal substrate;

[0059] In step 2), the ultrasonic rolling process parameters are: working static pressure is 450N, output amplitude is 10μm, spindle speed is 220r / min, lateral feed is 0.5mm / min, rolling times is 4 times, and the diameter of the rolling ball is 20mm;

[0060] 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0061] In step 3), the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the first alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon gas pressure 35Pa, time 3h, temperature 700℃; the source target material is composed of Ti, Co and Zr in a mass ratio of 2:1:4.5, and the diameter of the source target material is 40mm and the thickness is 3mm; the second alloying treatment adopts a double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon gas pressure 38Pa, the first period of time 2h, temperature 820℃, the second period of time 1h, temperature 780℃; the source target material is W, and the diameter of the source target material is 40mm and the thickness is 3mm;

[0062] 4) After the alloyed metal substrate is subjected to ion nitriding treatment, a metal finished product is obtained;

[0063] In step 4), the nitriding process parameters are: voltage 800 V, temperature 800° C., time 8 h, and the volume ratio of hydrogen to nitrogen is 3:1.

[0064] Comparative Example 1

[0065] Compared with Example 2, the difference is that the first alloying treatment is not performed, and the remaining preparation steps and parameters are the same.

[0066] Comparative Example 2

[0067] Compared with Example 2, the difference is step 3):

[0068] Step 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0069] In step 3), the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the first alloying treatment adopts a double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon gas pressure 35Pa, time 3h, temperature 685°C; the source target is composed of Ti, Co and Zr in a mass ratio of 2:1:3.8, and the diameter of the source target is 40mm and the thickness is 3mm; the second alloying treatment adopts a double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon gas pressure 38Pa, time 3h, temperature 810°C.

[0070] The rest of the preparation steps and parameters were the same.

[0071] Comparative Example 3

[0072] Compared with Example 2, the difference is step 3):

[0073] Step 3) performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate;

[0074] In step 3), the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the first alloying treatment adopts a double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon gas pressure 35Pa, time 3h, temperature 685°C; the source target is composed of Ti, Co and Zr in a mass ratio of 2:1:3.8, and the diameter of the source target is 40mm and the thickness is 3mm; the second alloying treatment adopts a double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 380V, inter-electrode spacing 30mm, argon gas pressure 38Pa, time 3h, temperature 765°C.

[0075] The rest of the preparation steps and parameters were the same.

[0076] Comparative Examples 4-6

[0077] Compared with Example 2, the difference is that the total mass of the source target material remains unchanged, the mass ratio of Ti, Co and Zr in the source target material is as shown in Table 1, and the other preparation steps and parameters are the same.

[0078] Table 1

[0079] Ti Co Zr Comparative Example 4 0 1 3.8 Comparative Example 5 2 0 3.8 Comparative Example 6 2 1 0

[0080] Thermal shock test

[0081] The metal products obtained in Examples 1-3 and Comparative Examples 1-6 were subjected to thermal shock tests respectively; the samples were heated from room temperature to a specified temperature, the test temperature was set at 900°C, and the heating rate was 10°C / min. After the samples were kept warm for 15 minutes, they were immediately put into 25°C water for quenching, dried, and then put into the furnace. The operation was repeated, and finally the samples were taken out for observation.

[0082] The test results are shown in Table 2.

[0083] Table 2

[0084]

[0085]

[0086] From the test results in Table 2, it can be seen that compared with Comparative Examples 1-6, the thermal shock resistance of the metal products prepared in Examples 1-3 of the present invention is significantly better than that in Comparative Examples 1-6, indicating that the interlayer bonding of the present invention is excellent.

[0087] Uniform corrosion test

[0088] The metal products obtained in Examples 1-3 and Comparative Examples 1-6 were subjected to uniform corrosion tests respectively; 10% hydrochloric acid was selected, the corrosion temperature was 50°C, and the corrosion time was 4 hours. The weight loss of the samples was calculated, and the results are shown in Table 3.

[0089] Table 3

[0090] Weight loss (mg) Example 1 1.2 Example 2 1.1 Example 3 1.3 Comparative Example 1 5.7 Comparative Example 2 2.5 Comparative Example 3 3.1 Comparative Example 4 3.9 Comparative Example 5 3.1 Comparative Example 6 3.7

[0091] From the test results in Table 3, it can be seen that compared with Comparative Examples 1-6, the corrosion resistance of the metal products prepared in Examples 1-3 of the present invention is significantly better than that in Comparative Examples 1-6.

[0092] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A metal surface treatment method, characterized in that: The processing method comprises the following steps: 1) adding a metal substrate into acetone for soaking, drying the metal substrate, adding anhydrous ethanol for ultrasonic treatment, and drying the metal substrate to obtain a clean metal substrate; 2) performing ultrasonic rolling on the clean metal substrate to obtain a pretreated metal substrate; 3) Performing secondary alloying treatment on the surface of the pretreated metal substrate to obtain an alloyed metal substrate; the secondary alloying treatment includes a first alloying treatment and a second alloying treatment; the metal elements of the first alloying treatment are Ti, Co and Zr; the metal element of the second alloying treatment is W; the first alloying treatment adopts double-layer glow ion metal diffusion technology, and the process parameters are as follows: source voltage 800V, workpiece voltage 350V, inter-electrode spacing 26mm, argon gas pressure 35Pa, time 3h, temperature 670-700℃ ; The source target material is composed of Ti, Co and Zr in a mass ratio of 2:1:3.0-4.5, with a diameter of 40 mm and a thickness of 3 mm; the second alloying treatment adopts double-layer glow ion metallization technology, and the process parameters are as follows: source voltage 800 V, workpiece voltage 380 V, inter-electrode spacing 30 mm, argon gas pressure 38 Pa, the first period of time 2 h, temperature 800-820 ° C, the second period of time 1 h, temperature 750-780 ° C; the source target material is W, with a diameter of 40 mm and a thickness of 3 mm; 4) After the alloyed metal substrate is subjected to ion nitriding treatment, a metal finished product is obtained.

2. A metal surface treatment method according to claim 1, characterized in that: In step 1), the mass ratio of the metal matrix, acetone and anhydrous ethanol is 12:45-60:50-65.

3. A metal surface treatment method according to claim 1, characterized in that: In step 1), the soaking time is 30-45 minutes; the ultrasonic treatment conditions are 40-50° C. temperature and 300-400 kHz ultrasonic wave for 5-10 minutes.

4. A metal surface treatment method according to claim 1, characterized in that: The metal matrix is ​​2Zr13 martensitic stainless steel.

5. A metal surface treatment method according to claim 1, characterized in that: In step 2), the ultrasonic rolling process parameters are: working static pressure is 350-450N, output amplitude is 8-10μm, spindle speed is 150-220r / min, lateral feed is 0.1-0.5mm / min, rolling times is 3-4 times, and the diameter of the rolling ball is 10-20mm.

6. A metal surface treatment method according to claim 1, characterized in that: In step 4), the nitriding process parameters are: voltage 800 V, temperature 800° C., time 8 h, and the volume ratio of hydrogen to nitrogen is 3:1.

Citation Information

Patent Citations

  • Method for depositing a wear coating on a high strength substrate with an energy beam

    US20100221448A1